Invasive Pneumococcal Disease in Children Can Reveal a Primary Immunodeficiency. (23rd April 2014) - Gaschignard, Jean; Levy, Corinne; Chrabieh, Maya; Boisson, Bertrand; Bost-Bru, Cécile; Dauger, Stéphane; Dubos, François; Durand, Philippe; Gaudelus, Joël; Gendrel, Dominique; Gras Le Guen, Christèle; Grimprel, Emmanuel; et al.
Abstract : The prospective inclusion of 163 children hospitalized in France for an invasive pneumococcal disease revealed that at least 10% of these children had a primary immunodeficiency. We advocate systematic immunological exploration for all children hospitalized for an invasive pneumococcal disease. Abstract : Background. About 10% of pediatric patients with invasive pneumococcal disease (IPD) die from the disease. Some primary immunodeficiencies (PIDs) are known to confer predisposition to IPD. However, a systematic search for these PIDs has never been carried out in children presenting with IPD. Methods. We prospectively identified pediatric cases of IPD requiring hospitalization between 2005 and 2011 in 28 pediatric wards throughout France. IPD was defined as a positive pneumococcal culture, polymerase chain reaction result, and/or soluble antigen detection at a normally sterile site. The immunological assessment included abdominal ultrasound, whole-blood counts and smears, determinations of plasma immunoglobulin and complement levels, and the evaluation of proinflammatory cytokines. Results. We included 163 children with IPD (male-to-female ratio, 1.3; median age, 13 months). Seventeen children had recurrent IPD. Meningitis was the most frequent type of infection (87%); other infections included pleuropneumonitis, isolated bloodstream infection, osteomyelitis, endocarditis, and mastoiditis. One patient with recurrent meningitis had a congenital cerebrospinal fluid fistula. The results of immunological explorations were abnormal in 26 children (16%), and a PID was identified in 17 patients (10%), including 1 case of MyD88 deficiency, 3 of complement fraction C2 or C3 deficiencies, 1 of isolated congenital asplenia, and 2 of Bruton disease (X-linked agammaglobulinemia). The proportion of PIDs was much higher in children aged >2 years than in younger children (26% vs 3%; P < .001). Conclusions. Children with IPD should undergo immunological investigations, particularly those aged >2 years, as PIDs may be discovered in up to 26% of cases.